"Gayl Jones's Corregidora :the black woman as a subject of history" - Šesnić, Jelena (Array, 2005)
Jones's 1975 neo-slave novel seems to be specific in the ways it uses and departs from generic expectations. Its strategy is, on one hand, to recuperate the black female body as a site of enunciative authority, and, on the other, to demonstrate how narrative performance based on the body can become entangled with the commodification of the body for the purposes of representing history. Jones attempts to show how performative speech-acts, such as narration, oral forms, the blues may present a new, and potentially more empowering, strategy for the speaking subject who is struggling to emerge through language. This aspect of the speech-act theory then can be seen as a segment of a wider phenomenon of performativity as it engages the production of historical discourse through the performance of witnessing, whereby the body and language are brought to work together.